Religious Activities and Environmental Concern in Communities in the Cibanten Watershed of Serang City - Sumintak Sumintak (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2022)
Natural resources and the environment are often neglected as targets of science that continue to be exploited. Environmental ethics is an attitude and responsibility that must be possessed by every human being towards his environment. There is a lot of environmental damage caused by human activities in both developed and developing countries. Islam as one of the religions that tries to realize the internalization of values ​​of concern for the environment must be carried out by humans as followers of religion. In the reality of daily life, humans will be very dependent on their natural environment, for example, human dependence on water (rivers). The behavior of people who throw garbage anywhere is suspected to be another factor causing flooding. This research examines how the community's religious activities are related to concern for the environment in efforts to prevent natural disasters such as floods which can maintain the sustainability of the community's environment in the Cibanten Watershed (DAS). This study uses a descriptive qualitative method of observing religious activities using an Interpretative Phenomenology approach observing every religious activity and practice of community environmental awareness as the object of research. The results of this study indicate that the religious activities of the people in the Cibanten River Basin (DAS) where the majority of the people are Muslims, from the religious activities of the people when viewed from their religious patterns are classified as inclusive and pluralist. Meanwhile, the activities of caring for the environment for the people who live in the Cibanten Watershed (DAS) are still very concerning. People tend to ignore the Cibanten River, for example, there are still many people who throw garbage into the Cibanten River.